Pengaruh Strategi Pembelajaran Berbasis Proyek Perancangan dan Kecerdasan Logik-Matematik Terhadap Kompetensi Merancang Web - Chandra Anugrah Putra (JTP - Jurnal Teknologi Pendidikan, 2016)
This study aims to determine the effect of learning strategies based design project for the competence of designing web, to determine the effect of intelligence logicalmathematical against the competence of designing web. The results showed that: (1) there are significant strategic project-based learning approach to the design of web designing competence; (2) there is the influence of logical-mathematical intelligence to web designingcompetence; (3) students who have the intelligence logical-mathematical high and use learning strategies based design projects programming language is higher than the group of students who have the intelligence logical-mathematical high and use learning strategies based design project content management system (CMS); (4) students which have logicalmathematical intelligence is low and using project-based learning strategies programming language design is lower than the group of students who have logical-mathematical intelligence is low and using project-based learning strategies designing content management system (CMS).